The Curriculum Reform of Design Education Based on the Orientation of Positive Psychology - Wu, Yi; Kyungsun, Kymn (Frontiers in Psychology, 2022)
At present, China With the rapid development, some problems and social contradictions have also become prominent. Therefore, many scholars call the current stage of Chinese society a transitional period. During the transition period of a country and nation, its education system will generally undergo corresponding reforms and transformations. And because of the advancement and foreseeability of the development of modern education, the reform and transformation of education must precede the reform and transformation of society, and the advancement and foresight of educational development must be ensured by the advancement and foresight of educational theories and thoughts. Moreover, this paper further examines the concept of cultivation grit, a culture of perseverance among the learners through a series of failures until victory. Cultivation grit is a fundamental personality trait that the modern education system of china needs to prioritize in the program. This paper systematically expounds on the approaches and methods of education curriculum reform. It conducts research and analysis on the design education curriculum reform based on positive psychology through field research, logical analysis, and other research methods. Experimental research shows that design education curriculum reform based on positive psychology orientation has better feasibility than traditional education curriculum reform.